Tartans in Thailand : Pernod Ricard's Thai Whisky War of 2007 - Hennessy, Julie; Frazzano, Rebecca; Meagher, Evan (London : SAGE Publications Ltd, 2017)
The case examines a competitive situation in the market for Scotch whisky in Thailand. Two multinationals fight for market share with a complex portfolio of products under the Chivas Regal, Johnnie Walker, and Ballantine brand names. Students must understand a broad array of branding, consumer behavior, pricing, and regulatory issues in order to arrive at recommendations for Chivas Regal to defend against recent gains of Johnnie Walker. The case can be taught with a focus on the Chivas Regal 12 Year product and recommendations for its growth, but also can be taught as a broader portfolio case, with students aligning a portfolio of Chivas and Ballantine products at different quality levels to maximize sales and profit.
Originally published: Hennessy, J., Frazzano, R., & Meagher, E. (2010). Tartans in Thailand: Pernod Ricard&s Thai whisky war of 2007. 5-210-251. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Whiskey industry -- Thailand -- Case studies; Alcoholic beverage industry -- Thailand -- Case studies; Branding (Marketing) -- Thailand -- Case studies